Antidepressant Controlled Trial For Negative Symptoms In Schizophrenia (ACTIONS): a double-blind, placebo-controlled, randomised clinical trial - Thomas RE Barnes; Verity C Leeson; Carol Paton; Céire Costelloe; Judit Simon; Noemi Kiss; David Osborn; Helen Killaspy; Tom KJ Craig; Shôn Lewis; Patrick Keown; Shajahan Ismail; et al. (Health Technology Assessment, 2016)
Background: Negative symptoms of schizophrenia represent deficiencies in emotional responsiveness, motivation, socialisation, speech and movement. When persistent, they are held to account for much of the poor functional outcomes associated with schizophrenia. There are currently no approved pharmacological treatments. While the available evidence suggests that a combination of antipsychotic and antidepressant medication may be effective in treating negative symptoms, it is too limited to allow any firm conclusions. Objective: To establish the clinical effectiveness and cost-effectiveness of augmentation of antipsychotic medication with the antidepressant citalopram for the management of negative symptoms in schizophrenia. Design: A multicentre, double-blind, individually randomised, placebo-controlled trial with 12-month follow-up. Setting: Adult psychiatric services, treating people with schizophrenia. Participants: Inpatients or outpatients with schizophrenia, on continuing, stable antipsychotic medication, with persistent negative symptoms at a criterion level of severity. Interventions: Eligible participants were randomised 1 : 1 to treatment with either placebo (one capsule) or 20 mg of citalopram per day for 48 weeks, with the clinical option at 4 weeks to increase the daily dosage to 40 mg of citalopram or two placebo capsules for the remainder of the study. Main outcome measures: The primary outcomes were quality of life measured at 12 and 48 weeks assessed using the Heinrich’s Quality of Life Scale, and negative symptoms at 12 weeks measured on the negative symptom subscale of the Positive and Negative Syndrome Scale. Results: No therapeutic benefit in terms of improvement in quality of life or negative symptoms was detected for citalopram over 12 weeks or at 48 weeks, but secondary analysis suggested modest improvement in the negative symptom domain, avolition/amotivation, at 12 weeks (mean difference –1.3, 95% confidence interval –2.5 to –0.09). There were no statistically significant differences between the two treatment arms over 48-week follow-up in either the health economics outcomes or costs, and no differences in the frequency or severity of adverse effects, including corrected QT interval prolongation. Limitations: The trial under-recruited, partly because cardiac safety concerns about citalopram were raised, with the 62 participants recruited falling well short of the target recruitment of 358. Although this was the largest sample randomised to citalopram in a randomised controlled trial of antidepressant augmentation for negative symptoms of schizophrenia and had the longest follow-up, the power of statistical analysis to detect significant differences between the active and placebo groups was limited. Conclusion: Although adjunctive citalopram did not improve negative symptoms overall, there was evidence of some positive effect on avolition/amotivation, recognised as a critical barrier to psychosocial rehabilitation and achieving better social and community functional outcomes. Comprehensive assessment of side-effect burden did not identify any serious safety or tolerability issues. The addition of citalopram as a long-term prescribing strategy for the treatment of negative symptoms may merit further investigation in larger studies. Future work: Further studies of the viability of adjunctive antidepressant treatment for negative symptoms in schizophrenia should include appropriate safety monitoring and use rating scales that allow for evaluation of avolition/amotivation as a discrete negative symptom domain. Overcoming the barriers to recruiting an adequate sample size will remain a challenge. Trial registration: European Union Drug Regulating Authorities Clinical Trials (EudraCT) number 2009-009235-30 and Current Controlled Trials ISRCTN42305247. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 20, No. 29. See the NIHR Journals Library website for further project information.